Correspondence testing studies - Dan-Olof Rooth (IZA World of Labor, 2021)
Anti-discrimination policies play an important role in public discussions. However, identifying discriminatory practices in the labor market is not an easy task. Correspondence testing provides a credible way to reveal discrimination in hiring and provide hard facts for policies, and it has provided evidence of discrimination in hiring across almost all continents except Africa. The method involves sending matched pairs of identical job applications to employers posting jobs—the only difference being a characteristic that signals membership to a group.
Keywords: D2; J1; J2; J7; 330; correspondence testing; taste-based discrimination; statistical discrimination